Developing a Mental Health Counseling E-book to Improve Student Mental Health - Sahputra, Dika; Fawri, Andika; Rapono, Muhammad; Asyfa, Amalya; Putra, Ardika Mandala (Mitra Ash-Shibyan: Jurnal Pendidikan dan Konseling, 2025)
The mental health of university students is a crucial aspect that contributes to their academic success and psychological well-being. However, many students experience academic, social, and emotional pressures that may trigger mental health disorders such as stress, anxiety, and depression. Unfortunately, limited access to counseling services and the negative stigma surrounding mental health discourage many students from seeking help. Therefore, innovative solutions are needed to support student mental health in a more accessible and effective manner. This study aims to develop and evaluate the effectiveness of a mental health counseling e-book for university students. The research employs the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) development model, involving 417 students from the State Islamic University of North Sumatra. Data collection was conducted using a Likert-scale questionnaire to measure students' mental health before and after the e-book intervention. The findings indicate that the developed e-book meets the content and design feasibility standards, with percentages of 68.73% and 88.52%, respectively, and was deemed highly suitable by experts. The Wilcoxon statistical test revealed a significant improvement in students' mental health levels following the use of the e-book, with an Asymp. Sig value of 0.000 (p < 0.05). Thus, the e-book has proven to be an effective tool in helping students manage their mental health. This study recommends the utilization of e-books as a supplementary counseling medium in higher education institutions to enhance students' psychological well-being.